Muqarnas: Ungkapan Keagungan Nilai Islam dalam Karya Arsitektur - Putrie, Yulia Eka (UIN Maulana Malik Ibrahim Malang, 2010)
Muqarnas is the Arabic word for stalactite vault, a three-dimensional decoration element in Islamic architecture. Inspired by honey comb, this kind of architectural ornament has been developed to the highest form of aesthetics and complexity. Its uniqueness is laid on its geometrical composition, which is transformed from thousands of cells, tiers and intermediate elements. Inspite of its amazing geometrical composition, there are some values and meanings that consist in muqarnas. Infinitive design of muqarnas is mostly based on human’s awareness of God’s infinite highness and strength. Furthermore, it shows us that Allah’s creation such as honey combs, that is often being underestimated by human, contain huge of knowledge and complicated calculations. These kind of awareness and wisdoms are yielded by artists and architects in the past, who had never detached science from Islam, as the way of life. Muqarnas adalah kata Arab untuk kubah stalaktit, elemen hiasan tiga dimensi dalam arsitektur Islam. Terinspirasi oleh sarang madu, ornamen arsitektur semacam ini telah berkembang menjadi bentuk estetika dan kompleksitas tertinggi. Keunikannya diletakkan pada komposisi geometrisnya, yang ditransformasikan dari ribuan sel, tingkatan dan elemen antara. Terlepas dari komposisi geometrisnya yang menakjubkan, ada beberapa nilai dan makna yang ada di muqarnas. Desain infinitif muqarnas sebagian besar didasarkan pada kesadaran manusia akan kekuatan dan kekuatan Tuhan yang tak terbatas. Lebih jauh lagi, ini menunjukkan kepada kita bahwa ciptaan Allah seperti sarang madu, yang sering diremehkan oleh manusia, mengandung banyak pengetahuan dan perhitungan yang rumit. Jenis kesadaran dan hikmat ini dihasilkan oleh seniman dan arsitek di masa lalu, yang tidak pernah melepaskan ilmu pengetahuan dari Islam, sebagai cara hidup.